Solanum tuberosum- An Appealing Alternative for Solanesol - Sharma, Manish (International Journal of Pharmaceutical & Biological Archive, 2010)
Highly purified Solanesol is well-sold raw material. It is found that highly purified Solanesol itself can be used either as a drug or intermediate. It is mainly used in synthesis of anticancer compounds, CoQ10 and vitamin K2. At present the market rate of Solanesol is around $300 per Kg. So the promise of reduced cost and bulk production makes S. tuberosum an appealing alternative for extraction of Solanesol.